Anaesthesiological provision for surgical interventions with the patient in a prone position (a review of literature) - Lyzogub, Mykola; Kostrikova, Eleanora; Khmyzov Andrеy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
The article reviews modern literature on problems of anaesthetic provision for surgical interventions with prone positions of patients. The authors thoroughly examine aspects of physiological changes, which occur in this surgical position, and possible complications. Variants of anaesthetic provision for patients in prone positions, advantages and disadvantages of some of its kinds are described separately.